Ultrathin Twisted Germanium Sulfide van der Waals Nanowires by Bismuth Catalyzed Vapor–Liquid–Solid Growth. Issue 51 (16th October 2021) - Sutter, Eli; Sutter, Peter
Abstract: 1D nanowires of 2D layered crystals are emerging nanostructures synthesized by combining van der Waals (vdW) epitaxy and vapor–liquid–solid (VLS) growth. Nanowires of the group IV monochalcogenide germanium sulfide (GeS) are of particular interest for twistronics due to axial screw dislocations giving rise to Eshelby twist and precision interlayer twist at helical vdW interfaces. Ultrathin vdW nanowires have not been realized, and it is not clear if confining layered crystals into extremely thin wires is even possible. If axial screw dislocations are still stable, ultrathin vdW nanowires can reach large twists and should display significant quantum confinement. Here it is shown that VLS growth over Bi catalysts yields vdW nanowires down to ≈15 nm diameter while maintaining tens of µm length. Combined electron microscopy and diffraction demonstrate that ultrathin GeS nanowires crystallize in the orthorhombic bulk structure but can realize nonequilibrium stacking that may lead to 1D ferroelectricity. Ultrathin nanowires carry screw dislocations, remain chiral, and achieve very high twist rates. Whenever the dislocation extends to the nanowire tip, it continues into the Bi catalyst. Eshelby twist analysis demonstrates that the ultrathin nanowires follow continuum predictions. Cathodoluminescence on individual nanowires, finally, shows pronounced emission blue shifts consistent with quantum confinement. Abstract : Germanium sulfide (GeS) van der Waals nanowires are of interest for twistronics due to their tunable interlayer twist. Using Bi as a vapor–liquid–solid growth catalyst extends the accessible diameters of GeS nanowires down to ≈15 nm while maintaining tens of µm in length. The ultrathin nanowires carry screw dislocations, are chiral, achieve high twist rates, and show pronounced quantum confinement.